Paraneoplastic Pemphigus: Autoimmune-Cancer Nexus in the Skin - A. Sinha, Animesh (Anti-Cancer Agents in Medicinal Chemistry, 2015)
Paraneoplastic pemphigus (PNP) is a debilitating and lethal adult and pediatric autoimmune blistering skin disease that occurs in the setting of a known or occult neoplasm. It is characterized by painful mucosal erosions that are often resistant to therapy. These clinical characteristics, in addition to positive immunohistochemistry findings make the diagnosis of PNP. The ability to recognize and diagnose PNP has dramatically improved in the last two and half decades. However, the mortality remains 75-90% with a mean survival of less than 1 year. The disease typically progresses from localized skin manifestations to multiple organ failure despite treatment with high dose corticosteroids and immunosuppressives. Because PNP has a low incidence and prevalence, information on treatment and management strategies has depended on a limited number of case reports and case series. The rarity of the disease hampers the ability to conduct large-scale clinical trials as well as investigations into the pathophysiology of PNP. In this article, we review clinical presentation, diagnosis, management, treatment, and pathophysiology of PNP.
Keywords: pemphigus